Komunikasi Fatis Bahasa Melayu Dialek Ambon Kabupaten Buru Selatan Kajian Sosiosemantik - Indrayani, Nanik (Jurnal Ilmiah Dikdaya, 2024)
South Buru Regency is a pemekaran district of Buru Regency on Buru Island, Maluku Province.This study aims to describe the linguistic phenomenon, namely "Fatis Category of Malay Language Ambonese Dialect at the South Buru Regency Secretariat Section Council Office". This research can be classified into qualitative descriptive research. The population of this study was all users of the language used by employees of the secretariat council office containing the fatis category. Data collection techniques through observation, free listening techniques, recording techniques, and recording techniques. The results showed that there are five functions of the fatis category including, the function of different fatis categories, namely: (1), confirming the conversation, (2), emphasizing the reason, (3), starting the conversation, (4), strengthening the intention, and (5), saying to the interlocutor or speech partner who gets or experiences something good. Furthermore, the results of the research on the fatis categories used by employees in the secretariat council office in the form of particles are "e", "ka", "is", "to", and "we". The categories of fatis in the form of words are: "to and goods", "jua", "shalom", "adong", "anae", "sio" and "lai and jua". The categories of fatis in the form of fatis phrases are: "dangke banya lai", "akang barang", and "itu akang suda". That is the fatis category contained in the conversations of employees of the South Buru District secretariat council office in the form of particles, words and phrases.